Two-Phase Lung Damage Mechanisms For COVID-19 Disease, and Driving Force and Selectivity in Leukecyte Recruitment and Migration - Wu Jianqing; Zha Ping (Journal of Respiratory Diseases, 2022)
To understand lung damages caused by COVID-19, we deduced two phases lung damage mechanisms. After the lungs are infected with COVID-19, the affected lung tissue swells and surface properties of pulmonary capillaries change, both contributing to an increased flow resistance of the capillaries. The initial damages are mainly fluid leakage in a limited number of involved alveoli. The increased vascular resistance results in retaining more white blood cells (“WBCs”) in pulmonary capillaries. Some of the WBCs may get into interstitial spaces. When more and more WBCs are dynamically retained, the vascular resistance of pulmonary capillaries further rises; and thus the overall vascular resistance of the lungs rises and pulmonary pressure rises. The rise in the pulmonary pressure in turn results in elevated capillary pressures. When pulmonary capillary pressures around the alveoli are sufficiently high, the elevated pressure causes interstitial pressures to change from normally negative values to positive values. The positive pressures cause fluid leakage to the alvoeli and thus degrade lung function. Tissue swelling, and occupation of WBCs in interstitial spaces and occupation of alvoelar spaces by leaked water result in reduced deformable and compressible spaces, and thus causes a further rise of the vascular resistance of the lungs. When the pulmonary pressure has reached a critical point as in the second phase, the blood breaks capillary walls and squeezes through interstitial spaces to reach alveolar spaces, resulting in irreversible lung damages. Among potential influencing factors, the available space in the thorax cage, temperature, and humid are expected to have great impacts. The free space in the thorax cage, lung usable capacity, and other organ usable capacities are the major factors that determine the arrival time of last- phase irreversible damage. The mechanisms imply that the top priority for protecting lungs is maintaining pulmonary micro-circulation and preserving organ functions in the entire disease course while controlling viral reproduction should be stressed in the earliest time possible. The mechanisms also explain how leukecytes are “recruited and migrated” into inflamed tissues by dynamic retention.
Keywords: Coronavirus COVID-19